Avaliação de polimorfismos genéticos e a dose terapêutica da varfarina em pacientes com trombose: um estudo de coorte - Vanessa Cristina de Oliveira (2014)
The treatment of thromboembolic diseases aims to maintain a stable and personalized anticoagulation, for which the warfarin anticoagulant is the treatment of choice. The influence of several factors on the action of warfarin results in a wide variability in the patients response, and monitoring and appropriate dose adjustment require depth knowledge of these factors. The aim of this study was to investigate the association of polymorphisms CYP2C9*2 and CYP2C9*3, -1639G>A VKORC1, 3435C>T MDR1, APOE*4 and UGT1A1(TA)7/7 with the dose of warfarin required by 116 individuals in therapy anticoagulant. We observed that 20.7% of patients demonstrated requirements over 70 mg/week warfarin and, thus, they were resistant to warfarin. The BMI, the use of warfarin antagonists and 3435TT MDR1 and UGT1A1(TA)7/7 genotypes showed relationship with higher warfarin doses to achieve adequate anticoagulation therapy; which may contribute to the development of warfarin resistance. In contrast, increasing age, the CYP2C9*2 and CYP2C9*3 variants, -1639A VKORC1 and APOE*4 allele contribute to lower warfarin dose requirements. These results show that genetic factors may influence the variability in warfarin dose in this population and should be investigated in order to better adapt the anticoagulant treatment.